Impact of health technology assessment on prescribing patterns of inhaled fixed-dose combination triple therapy in chronic obstructive pulmonary disease. Issue 1 (1st January 2021) - Cook, Jennifer; Bloom, Chloe; Lewis, Jen; Marjenberg, Zoe; Platz, Jaime Hernando; Langham, Sue
ABSTRACT: Background : Evidence suggests that triple therapy for patients with chronic obstructive pulmonary disease (COPD) is being used in a broader range of patients than recommended by guidelines, which may have health and cost implications. Objective : To explore the relationship between national health technology assessment (HTA) agency appraisals and market penetration of two fixed-dose combination (FDC) triple therapies. Study design : HTAs from Q3 2017 to Q1 2020 from 10 countries were evaluated. Intervention : Glycopyrronium bromide/formoterol fumarate/beclomethasone (Trimbow®) and umeclidinium/vilanterol/fluticasone furoate (Trelegy™ Ellipta®). Main outcome measure : HTA restrictions and prescribing rates (days of therapy). Results : Seven countries (70%) imposed restrictions on use including prescription only for patients stable on free-combination triple therapy or not controlled on dual therapy, requirement of a specialist prescription or therapeutic plan, prescription only for patients with severe COPD, and use as second-line therapy or later. In general, countries that have imposed restrictions on the use of FDC triple therapies have seen a lower than average uptake. Conclusion : Payer guidance on prescribing FDC triple therapy may potentially support more appropriate prescribing in line with clinical guidelines. It is important for payers to consider which restrictions would ensure the most efficient use of scarce resources.